Smart City’s Internationalization and International Management Strategies in the Digital Era: A Systematic Literature Review - Marchesani, Filippo; Iaia, Lea; Masciarelli, Francesca; Christofi, Michael (My University, 2023)
The impact of the smart city concept in the urban landscape has been the subject of considerable attention over the last few years. Cities are changing their development strategies by trying to attract not only capital but also knowledge and talent. This change has led cities to turn increasingly to the outside world by developing international strategies and raising their internationalization process towards the global context. The purpose of the paper is to develop a systematic overview of the literature examining the relationship between smart cities and the internationalization process. Emphasis will be placed on global management strategies for the international development of smart cities. The study aims to examine existing research through the adaptation of the Systems Literature Review (SLR). As a result, new knowledge on the state of the art in policy, practice, and academia can be generated to identify significant theoretical insights and knowledge gaps for future research. We provide a descriptive analysis, a state of the art of research topic, and an integrative vision of the development of smart cities concerning international management and the internationalization process.
Keywords: International strategies; Internationalization; Smart cities; Systematic literature review